2014
DOI: 10.1186/s12917-014-0295-3
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of Neospora caninum and Toxoplasma gondii antibodies in dogs in Jilin, Henan and Anhui Provinces of the People’s Republic of China

Abstract: BackgroundNeospora caninum and Toxoplasma gondii are important pathogens of worldwide distribution. N. caninum is a major cause of abortion in cattle and dogs are main reservoirs because they excrete the environmentally resistant oocysts. Toxoplasmosis is a worldwide zoonosis and dogs are considered as sentinels for this parasite because of their close contact with people and cats; additionally dog meat is also used for human consumption in China. The aim of the present study was to assess the prevalence of N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…There are reports on the occurrence of canine neosporosis in various parts of the world, with seroprevalence levels ranging from 0% to 32% being reported [1,2,8,14-17]. A previous Kenyan study reported that out of 140 dogs screened, none was seropositive to NC [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are reports on the occurrence of canine neosporosis in various parts of the world, with seroprevalence levels ranging from 0% to 32% being reported [1,2,8,14-17]. A previous Kenyan study reported that out of 140 dogs screened, none was seropositive to NC [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this area, most of the owners allow their dogs to roam outside the home, which presumably places them in closer contact with other sources of animal products and allows exposure to T. gondii oocytes from freely roaming cats. Nevertheless, it was found that the seroprevalence of T. gondii in dogs in this area was lower than that in most other parts of China [25], perhaps because since 2002 the owners of dogs in Shanghai have been supplied a sulpha drug free of charge by the animal health authorities [16].…”
Section: Discussionmentioning
confidence: 76%
“…Antibodies to N. caninum have been reported in dogs worldwide [ 21 , 28 , 29 ]. There have also been some surveys of N. caninum infections in dogs in some provinces or cities of China in recent years ( Table 1 , [ 1 , 16 , 18 , 19 , 26 , 30 , 32 , 35 ]). However, little information is available on the epidemiology of N. caninum infections in dogs in central China.…”
Section: Introductionmentioning
confidence: 99%
“…However, little information is available on the epidemiology of N. caninum infections in dogs in central China. In 2014, Yang et al reported the infection rate of N. caninum in dogs from Henan province to be 0.0% (0/31) [ 35 ]. But only 31 serum samples of dogs from Henan province were tested for antibodies to N. caninum in Yang et al’s study [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation